THE IMPLEMENTATION STRATEGY FOR THE SUPPRESSION OF THE COMMUNIST PARTY OF MALAYA (CPM) IN THAILAND: THE CASE STUDY OF TAI ROM YEN POLICY - Inkum, Thippaporn; Ho Hui Ling (SEJARAH: Journal of the Department of History, 2025)
During the Cold War era, the communist insurgency was viewed as a critical threat to national security for the Royal Thai Government, especially the Communist Party of Thailand (CPT). Nevertheless, throughout the period of Communist insurgency in Thailand (1965-1983), the Communist Party of Malaya (CPM) also emerged as a Communist movement that challenged the Thai State in the southern region. This article aims to understand the policy and implementation strategy of Thai government to deal with the CPM even was a significantly reduced danger in relation to the Communist uprising in Thailand. The Study found that the “Tai Rom Yen” (Tranquil south) Policy was the first steps in the political offensive against the communist movement in the south and also a clear demonstration of the implementation of the Order of the Office of the Prime Minister No. 66/2523 (Order No. 66/2523). This policy represented a significant effort to address the violent circumstances in the south, and the Thai government considered that popular support must be central to its anti-communist strategies. As a result, the execution of the policy resulted in garnering public favour, which was crucial for securing the ultimate triumph over the communists and their eventual disbandment.